2012
DOI: 10.1111/j.1445-2197.2012.06174.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of video-assisted thoracoscopic resection for posterior mediastinal neurogenic tumours: a retrospective analysis of 58 patients

Abstract: Video-assisted thoracoscopic resections of the posterior mediastinal tumours were safe and reliable for selected patients with mastered thoracoscopic skills. Intracapsular enucleation was demonstrated to be a safe procedure. For tumours larger than 6 cm and located in the apex, the risk of the operation increased significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
0
26
0
3
Order By: Relevance
“…En la presente serie de casos, los pacientes con tumor de mediastino fueron la mayoría de sexo masculino, en relación con los artículos publicados por la comunidad científica [3][4][5][6]. En cuanto a la edad, aunque se reporta que se presenta en cualquier etapa de la vida, en este reporte en los 5 años del registro, la edad media de estos pacientes es de 60 años.…”
Section: Discussionunclassified
“…En la presente serie de casos, los pacientes con tumor de mediastino fueron la mayoría de sexo masculino, en relación con los artículos publicados por la comunidad científica [3][4][5][6]. En cuanto a la edad, aunque se reporta que se presenta en cualquier etapa de la vida, en este reporte en los 5 años del registro, la edad media de estos pacientes es de 60 años.…”
Section: Discussionunclassified
“…The use of a VATS approach was first reported in 1992 by Landreneau et al (61) and since then, it has become the preferred technique (62-68) because it greatly improves operative visualization making surgery easier and safer. In addition, VATS reduces the amount of postoperative pain and shoulder girdle dysfunction resulting in better functional outcomes (57,69). Neurogenic tumors are indeed ideally suited for VATS resection because the majority are small and well encapsulated (Figure 4).…”
Section: Surgical Approach and Thoracoscopic Techniquesmentioning
confidence: 99%
“…Port placement depends on tumor location and most surgeons recommend the use of three triangulated ports. Since most neurogenic tumors have a well-defined capsule, they can be resected by simple enucleation (68) with intercostal and paravertebral blood vessels being ligated, clipped, or coagulated with advanced bipolar cautery or ultrasonic energy devices (59,69). The pedicle of the tumor, which is usually the intercostal nerve, is then divided on both sides of the tumor.…”
Section: Surgical Approach and Thoracoscopic Techniquesmentioning
confidence: 99%
“…According to the dimension, Li and Wang (17) reported their experience with 58 patients. They established a cut off of 6 cm for tumors of the apex to undergo easy and complete thoracoscopic resection, over which operative time, blood loss and the incidence of post-operative complications were increased, and concluded that tumor diameter is the principal determinant for surgical indication to VATS (17). Conversely, a recent experience by Ciriaco and co-workers (8) demonstrated the excision of 7-8 cm posterior mass via thoracoscopic surgery, simply enlarging one of the thoracoscopic access, and using an endo-bag to facilitate the passage through the incision and avoiding seeding.…”
mentioning
confidence: 99%
“…This vessel, also called arteria radicularis magna, origins from the posterior branches of the intercostal arteries at a level that varies mainly between T8 and L1 with major incidence on the left side (70%) (18). Loss of this artery could lead to spinal cord injuries or ischemia (10,17). A coordinated approach with neurosurgeons is important for a successful excision of these tumors and better outcome.…”
mentioning
confidence: 99%